2015
DOI: 10.1186/s12896-015-0178-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural phenolics greatly increase flax (Linum usitatissimum) oil stability

Abstract: BackgroundFlaxseed oil is characterized by high content of essential polyunsaturated fatty acids (PUFA) promoted as a human dietary supplement protecting against atherosclerosis. The disadvantage of the high PUFA content in flax oil is high susceptibility to oxidation, which can result in carcinogenic compound formation. Linola flax cultivar is characterized by high linoleic acid content in comparison to traditional flax cultivars rich in linolenic acid. The changes in fatty acid proportions increase oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 53 publications
4
30
0
Order By: Relevance
“…The study conducted by Siger et al 51 showed that p-hydroxybenzoic, vanillic and ferulic acids are the major phenolic acids that are presented in the flaxseed oil, while Tuberoso et al 46 found only vanillic acid. On the other hand, Hasiewicz-Derkacz et al 8 found that vanillin is the most abundant phenolic compound in flaxseed oil. The other components are non-hydrolysable proanthocyanidins and hydrolysable tannins, p-coumaric acid, ferulic acid, caffeic acid, coniferyl and syringic aldehyde, and small amount of flavonoids.…”
Section: Content Of Bioactive Compounds In Fresh Axseed Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by Siger et al 51 showed that p-hydroxybenzoic, vanillic and ferulic acids are the major phenolic acids that are presented in the flaxseed oil, while Tuberoso et al 46 found only vanillic acid. On the other hand, Hasiewicz-Derkacz et al 8 found that vanillin is the most abundant phenolic compound in flaxseed oil. The other components are non-hydrolysable proanthocyanidins and hydrolysable tannins, p-coumaric acid, ferulic acid, caffeic acid, coniferyl and syringic aldehyde, and small amount of flavonoids.…”
Section: Content Of Bioactive Compounds In Fresh Axseed Oilsmentioning
confidence: 99%
“…According to research of This modification significantly contributed to improving the stability of the oil. Moreover, climate in northern Europe is highly suitable for the production of Linola seeds 8 . Diversity in the composition of fatty acids in the oils can also be caused by environmental and growing conditions 33 .…”
Section: Fatty Acid Composition Of Fresh Axseed Oilsmentioning
confidence: 99%
“…Both the collected methanol extracts and combined ethyl acetate extracts were dried under nitrogen flow, resuspended in methanol and analyzed using UPLC (Waters Acquity UPLC) system with a 2996 PDA QTOF mass detector on an Acquity UPLC BEH C18 (2.1 × 100 mm, 1.7 μm) column. The mobile phase was 0.1% formic acid and 100% acetonitrile (Hasiewicz-Derkacz et al 2015).…”
Section: Quantitative Analysis Of Phenolic Compoundsmentioning
confidence: 99%
“…Flaxseed is one of the most commonly used seed in human diet, recognized as a supplement for its beneficial properties due to its high content of PUFAs, secoisolariciresinol diglucoside, phenolic acids and flavonoids. Phenolic compounds as other secondary metabolites are beneficial to the embryonic plant in their constitution in order to prevent degradation of fatty acids and other nutrients during seed storage [217].…”
Section: From Seedsmentioning
confidence: 99%